ORIENTASI MUTU PENDIDIKAN MANAJEMEN BERBASIS SEKOLAH - Kadarisman Kadarisman; Saifullah Idris (Jurnal MUDARRISUNA: Media Kajian Pendidikan Agama Islam, 2019)
Improving the quality of human resources is an absolute prerequisite for achieving development goals. Efforts to improve the quality of education are continuously carried out. It is even more focused after being mandated in the objectives of national education, namely to improve the quality of education at each type and level of education. Realizing this, the government has made efforts to improve the education system, both through structuring software (software) and hardware (hardware). For this reason, attention needs to be paid to improving the quality of education. In this case, using the School-Based Management (MBS) approach. MBS can be regarded as a community work process by applying the principles of autonomy, accountability, participation, and sustainability to achieve quality education and learning goals.